Africa PID Alliance Digital Object Identifiers Registration Concept Note - Ksibi, Nabil; Owango, Joy; Sara (My University, 2023)
Persistent Identifiers are the pillars of an interoperable, persistent and reliable Open Research Infrastructure. This is the reason why a lot of countries/regions and organizations took the initiative to contribute to this network and help promote the use of PIDs through their academic and publishing ecosystems.
Keywords: Open Research; INTERDISCIPLINARY RESEARCH AREAS::Cultural heritage and cultural production; Indeginous Knowledge